RETORIKA STORYTELLER KOMUNITAS WALKING TOUR “MLAKU MAGELANG” DALAM MENGENALKAN TEMPAT BERSEJARAH DI KOTA MAGELANG - Ibda Fikrina Abda; Eny Ratnasari (Universitas Tidar, 2025)
This study aims to examine the rhetoric of the storyteller “Mlaku Magelang” storyteller in introducing historical places in Magelang. Using a qualitative approach, this research explores how storytellers use Aristotle’s rhetorical principles, namely Invention, Arrangement, Style, Delivery, and Memory, to convey interesting and educational historical narratives to tourists. Through observations and interviews with founders and tourists, it was found that the use of casual language, different costumes according to the route, and interactions involving humor contribute to an immersive tourist experience. The results indicate that storytellers who fulfill the aspect of Aristotle’s rhetoric in conveying narratives not only enrich historical understanding, but also build emotional connection between tourists and the places visited. This study is expected to contribute to the development of communication strategies in tourism, particularly in the context of walking tours.